LINGVISTIK TADQIQOTLARDA STATISTIK METODNING O‘RNI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
At the beginning of the 21st century, due to the rapid development of information technologies, not only the process of globalization, but also the education system rose to new levels. At this stage, all fields, especially science, require rapid development. Therefore, it is important to rely on the computer and technical capabilities rather than the human factor. As a result, linguistics and linguistics merged, and the field of computational linguistics was formed and is developing. This thesis presents some comments on the role and development of the statistical method for computer linguistics.
Keywords: statistics, statistical method, frequency dictionary, SAS (Statistical Analysis Software).